Thoughts on interaction design - Kolko, Jon (Morgan Kaufmann, 2011)
Thoughts on Interaction Design, Second Edition, contemplates and contributes to the theory of Interaction Design by exploring the semantic connections that live between technology and form that are brought to life when someone uses a product. It defines Interaction Design in a way that emphasizes the intellectual and cultural facets of the discipline. This edition explores how changes in the economic climate, increased connectivity, and international adoption of technology affect designing for behavior and the nature of design itself. Ultimately, the text exists to provide a definition that encompasses the intellectual facets of the field, the conceptual underpinnings of interaction design as a legitimate human-centered field, and the particular methods used by practitioners in their day-to-day experiences. This text is recommended for practicing designers: interaction designers, industrial designers, UX practitioners, graphic designers, interface designers, and managers.